[Syllabuses, 1966-68, 1973-74) - Papua and New Guinea. Department of Education ([Konedobu, Papua : Territory of Papua and New Guinea, 1966)
Secondary school syllabi for a number of different subjects.
Spine title.
Keywords: Education, Secondary -- Papua-New Guinea -- Curricula